Precision oncology for breast cancer through clinical trials - Blucher, Aurora S.; Mills, Gordon B.; Tsang, Yiu Huen (Clinical & experimental metastasis, 2022)
Precision treatment for breast cancers has made several notable advances in recent decades, but challenges of tumor heterogeneity, drug resistance, and aggressive recurrence and metastases remain. To meet and overcome these challenges, we must refine our understanding of breast subtypes and treatment biomarkers according to the knowledge afforded across the spectrum of ‘omics assays. A critical aspect of harnessing this knowledge into actionable biomarkers for treatment decision relies on our ability to integrate knowledge across data types and leverage our insight in evidence-based clinical trials. We review recent advances in cutting-edge clinical trials for precision treatment of breast cancer, including chemotherapies, targeted therapies, immunotherapies, and combination therapies. We comment on promising future areas of development for this exciting point in precision breast cancer research.